Simulation Of Bobbin Friction Stir Welding Using Deform-3D - Mohammed AbdulGhaffar, Firas Ahmed (2018)
Bobbin Friction Stir Welding is a relatively new solid-state process and a variation of Friction Stir Welding (which was invented and patented by The Welding Institute) that distinguishes itself in terms of tool structure, characteristics and advantages. Despite the lack of sufficient understanding of this process, Bobbin Friction Stir Welding is known to surpass conventional welding because its double-sided feature contributes to low thermal distortion, reduces down force, eliminates root causes and produces better quality welds with strong mechanical structure. Bobbin Friction Stir Welding tool consists of two cylindrical shoulders connected by a pin, all of them contact the work-piece. The tool penetrates two joined metal plates at the joint-line, which heats the material. When plastic state is achieved, the softened material of the each plate is mixed with the other, forming a solid bond at the solid state. There is still a relative shortage of literature concerning the mechanism of this process. Therefore, the goal was to contribute to the existing research findings by investigating this welding process. The objective of this project was to analyze temperature behavior and flow of work-piece material during the welding process at different welding parameters, utilizing Finite Element Analysis and DEFORM-3D software for simulation, and validate the results by comparison with previous study. A three-dimensional, Finite Element Model of the bobbin friction stir welding tool and work-piece was developed and evaluated using DEFORM-3D software tool. Welding speeds were varied throughout the simulation, and the simulation results were compared with those obtained by previous researchers. Additionally, several past studies on the subject of both conventional and bobbin friction stir welding were analyzed for validation purposes. The findings of this analysis revealed that temperature profile was symmetric along the X-Y axis as the tool moves along the work-piece, while in the X-Z section it exhibited symmetry of wide distribution at the surfaces of the work-plates and narrow radius about the mid-thickness, forming a „waist shape‟. Furthermore, the findings also indicated that sufficient welding temperature was achieved slower when the welding speed increased in each simulation run. Finally, the plastic material was observed to form a tail as it flowed outward towards the rear of the work-piece. These observations were reinforced and validated by other similar studies.